Management of penile cancer - Culkin, Daniel J. (Springer New York, 2014)
Management of Penile Cancer provides a comprehensive and state-of-the-art overview of the major issues specific to the field of penile cancer. The sections of the book are structured to review the overall scope of issues of penile cancer, including diagnosis and staging, surgical approaches, and the treatment of advanced disease. As multidisciplinary care is an integral part of the treatment of penile cancer, this book is unique in the inclusion of collaborating authors from a variety of integrated disciplines, including urology, radiation oncology, medical oncology, and reconstructive surgery   Written by recognized experts in their field, Management of Penile Cancer is a unique and valuable resource in the field of penile cancer, both for those currently in training and for those already in clinical or research practice.